Changes in mortality inequalities across occupations in Japan: a national register based study of absolute and relative measures, 1980-2010. Issue 9 (5th September 2017) - Tanaka, Hirokazu; Toyokawa, Satoshi; Tamiya, Nanako; Takahashi, Hideto; Noguchi, Haruko; Kobayashi, Yasuki
Abstract : Objective: Changes in mortality inequalities across socioeconomic groups have been a substantial public health concern worldwide. We investigated changes in absolute/relative mortality inequalities across occupations, and the contribution of different diseases to inequalities in tandem with the restructuring of the Japanese economy. Methods: Using complete Japanese national death registries from 5 year intervals (1980–2010), all cause and cause specific age standardised mortality rates (ASMR per 100 000 people standardised using the Japanese standard population in 1985, aged 30–59 years) across 12 occupations were computed. Absolute and relative inequalities were measured in ASMR differences (RDs) and ASMR ratios (RRs) among occupations in comparison with manufacturing workers (reference). We also estimated the changing contribution of different diseases by calculating the differences in ASMR change between 1995 and 2010 for occupations and reference. Results: All cause ASMRs tended to decrease in both sexes over the three decades except for male managers (increased by 71% points, 1995–2010). RDs across occupations were reduced for both sexes (civil servants 233.5 to −1.9 for men; sales workers 63.3 to 4.5 for women) but RRs increased for some occupations (professional workers 1.38 to 1.70; service workers 2.35 to 3.73) for men and decreased for women from 1980 to 2010. Male relative inequalities widened among farmer, fishery and service workers, because the percentage declines were smaller in these occupations. Cerebrovascular disease and cancer were the main causes of the decrease in mortality inequalities among sexes but the incidence of suicide increased among men, thereby increasing sex related inequalities. Conclusions: Absolute inequality trends in mortality across occupations decreased in both sexes, while relative inequality trends were heterogeneous in Japan. The main drivers of narrowing and widening mortality inequalities were cerebrovascular disease and suicide, respectively. Future public health efforts will benefit from eliminating residual inequalities in mortality by considering the contribution of the causes of death and socioeconomic status stratification.